Regulation of apoptosis of dendritic cells by il-10 and in association with stat-1 signaling molecule - Thuy, Nguyen Thu; Xuan, Nguyen Thi (Academia Journal of Biology, 2019)
IL-10 is an anti-inflammatory cytokine, participating in induction of immune tolerance and cell apoptotic death. Dendritic cells (DCs) is the most professional antigen-presenting cells among innate immune cells to exert generation and maintenance of immunological memory mediated through activation of T and B lymphocytes. The STAT signalling pathway plays a regulatory role of maturation and differentiation of immune cells. In this study, DCs were treated with inflammatory cytokines including TNF-a, INFg, IL-2 and IL-10 and subsequently examined the phosphorylation of STAT-1 and STAT-3, TNF-α concetration in cell suspension and the proportion of Annexin V+ and caspase 3+ cells. Methods used for this investigation include western blotting, flow cytometry and ELISA. DCs were derived from mouse bone marrow cells and cultured with GM-CSF for 8 days. As a result, IL-10, but not other cytokines enhanced the number of Annexin V+cells and caspase 3 activity in DCs. More importantly, IL-10 also increased the phosphorylation of STAT-1 as well as the release of TNF-α into cell suspension. In conclusion, activation of STAT-1 might relate to the cell apoptotic death and TNF-α sectetion in IL-10-treated DCs.